2011
DOI: 10.4028/www.scientific.net/amr.383-390.7138
|View full text |Cite
|
Sign up to set email alerts
|

On the Mechanism of the Effect of the Cryogenic Treatment on High Speed Steels

Abstract: The effect of subzero treatment on tool steels is well known, and is commercially practiced for certain varieties of tool steels. Substantial research is being carried out on the behavior of tool steels after cryogenic treatment (CT). While it has been established that CT improves the wear properties in some steels, the mechanism of this behavioral aspect is not yet fully known. Most work has been focused on AISI M2 high speed steel related to the effect on different properties, but the microstructural change … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The work of Chandrashekhar Gogte (author of this work) et al [10] has shown the presence of eta carbide in the cryogenically treated AISI T42 high speed steel. The present work comprises of the extension of the earlier work [10] and analyzes the fine carbide precipitation in cryogenically treated AISI T42 high speed steel.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…The work of Chandrashekhar Gogte (author of this work) et al [10] has shown the presence of eta carbide in the cryogenically treated AISI T42 high speed steel. The present work comprises of the extension of the earlier work [10] and analyzes the fine carbide precipitation in cryogenically treated AISI T42 high speed steel.…”
Section: Introductionmentioning
confidence: 75%
“…The experimental details can be referred to in the reference [10]; the details can be summarized as follows -AISI T42 ( Table 2) samples were conventionally hardened and tempered and subjected to cryogenic treatment for different soaking periods (8,16 and 24 hours). Low temperature tempering was carried out at 150 0 C. The samples soaked for 8 hours indicated best wear resistance.…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, the microstructure of −196 °C-treated steel reveals the presence of SGCs which are evenly distributed in the entire bulk of the material and their number is much higher than in the case of −110 °C-treated steel. Examinations of other high-speed steels, such as AISI M3:2 [61,170], AISI M35 [61,256,[311][312][313], AISI T42 [209,311], or S390 Microclean [165], have not provided a specification for the optimal combination of CT parameters to obtain the highest possible number of carbides because the results differ greatly. Moreover, no effect of CT on the carbide population was reported in some cases for AISI M3:2, S390 Microclean [167,168], or AISI M35 grade [121].…”
Section: High-speed Steelsmentioning
confidence: 99%
“…This finding may indicate an accelerated precipitation of transient carbides in cryogenically treated steel, which is demonstrated by the presence of spinodal decomposition, while no presence of such a decomposition is present in CHT steel. [61,256,[311][312][313], AISI T42 [209,311], or S390 Microclean [165], have not provided a specification for the optimal combination of CT parameters to obtain the highest possible number of carbides because the results differ greatly. Moreover, no effect of CT on the carbide population was reported in some cases for AISI M3:2, S390 Microclean [167,168], or AISI M35 grade [121].…”
Section: High-speed Steelsmentioning
confidence: 99%